A new locality of Koeneniodes madecassus Remy, 1950 (Palpigradi: Eukoeneniidae) in China, with the first complete redescription of a Koeneniodes species - Bu, Yun; Souza, Maysa Fernanda Villela Rezende; Ferreira, Rodrigo Lopes (Zootaxa, 2019)
Koeneniodes madecassus Remy, 1950 is reported from Guangxi Province, Southwest China for the first time. Since there has been neither a Koeneniodes record nor any morphological addendum since 1997, several traits used in contemporary palpigrade taxonomy have remained unknown for this genus. Here, we redescribe K. madecassus according to modern standards and provide information on the chaetotaxy of the pedipalp and the four legs, the shape of setae on the body, and some relevant measurements and indices. The geographical distribution of the species is outlined and discussed.